The Students` Perception About Use of Duolingo Application for Improving English Vocabulary - Anisa Dwi Tiara; M Arinal Rahman; Ciptro Handrianto (Peneliti.net, 2021)
The various challenges in education today require that the instructors should employ technology to make teaching English more appealing. Technology can serve as an alternative way to help students in learning English vocabulary. Vocabulary is one of the essential things for helping students in rich reading, listening, speaking, and writing skills. Nevertheless, there is a teacher who cannot use technology to support the teaching and learning process. This article aims to discuss and review previous studies about using the Duolingo application as one of the applications that supported students in English vocabulary. This article also provides information about the previous student perception of the Duolingo application to help students learn English vocabulary.